Behaviorism: Psychological Theory of Learning - Anita Fatimatul Laeli (Universitas Muhammadiyah Jember, 2020)
Learning theory is a very fundamental, systematic and comprehensive understanding of the process of how people particularly students, learn. Learning theory is much influenced by psychological theories. One of them is behaviorism theory. This theory believes that learning is a change in a person's behavior and that behavior can be observable and measured. This article aims to discuss the key concept in behaviorism, important figures in behaviorism, and how it is implemented in learning activity in the classroom. There are four concepts of behaviorism theory that are formulated by different psychologists; connectionism, classical conditioning, contiguous conditioning and operant conditioning. Every concept has different perspective on how the process of behavior change as a result of learning. However, in their implementation of activities, they have the same focus on learning activities; stimulus and response. The discussion of this paper starts with the key concept of behaviorism from different experts. Then, followed by how behaviorism implemented in the learning which can be in the form of teaching activities and assessment. Learning activities that may be the implementation of behavioristic theory include learning using PowerPoint and multimedia, or evaluation of learning that requires true and false answers /yes or no question. This paper is expected to give a clear insight for educators in understanding and implementing behaviorism as psychological theory of learning.